The Effect of Social Support and Self-Efficacy on Career Decision-Making of Final-Year Students at Aisyiyah University of Yogyakarta - Dzahwalun -; Annisa Warastri (Psikologi Prima, 2025)
This study aims to examine how social support and self-efficacy influence the career choices of students currently completing their studies at Aisyiyah University, Yogyakarta. This study used a quantitative method with a correlational approach and involved 101 students selected through purposive sampling. Data were analyzed using multiple linear regression. The findings of this study indicate that social support and self-efficacy have a significant influence on career choices. Social support has a greater impact than self-efficacy. Together, these two factors explain 65.5% of the change in students' career decisions.